2017
DOI: 10.1371/journal.pone.0177391
|View full text |Cite
|
Sign up to set email alerts
|

Bycatch in the Maldivian pole-and-line tuna fishery

Abstract: Tropical tuna fisheries are among the largest worldwide, with some having significant bycatch issues. However, pole-and-line tuna fisheries are widely believed to have low bycatch rates, although these have rarely been quantified. The Maldives has an important pole-and-line fishery, targeting skipjack tuna (Katsuwonus pelamis). In the Maldives, 106 pole-and-line tuna fishing days were observed between August 2014 and November 2015. During 161 fishing events, tuna catches amounted to 147 t: 72% by weight was sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…A majority of the catch from pole-and-line fisheries comes from fisheries where some of the fishing effort occurs on anchored FADs 35 , 44 – 48 , 66 ,89 . Some tuna pole-and-line fisheries also fish on drifting FADs, likely deployed by tuna purse seine fisheries 44 , 47 , 66 , 67 . While FADs are also used by some handline, jig, troll and driftnet fisheries 44 – 46 , 64 , 68 , this study did not include FADs as part of the assessment of risks from ALDFG for these gear types as it is unclear what proportion of global effort by these gears occurs on FADs.…”
Section: Methodsmentioning
confidence: 99%
“…A majority of the catch from pole-and-line fisheries comes from fisheries where some of the fishing effort occurs on anchored FADs 35 , 44 – 48 , 66 ,89 . Some tuna pole-and-line fisheries also fish on drifting FADs, likely deployed by tuna purse seine fisheries 44 , 47 , 66 , 67 . While FADs are also used by some handline, jig, troll and driftnet fisheries 44 – 46 , 64 , 68 , this study did not include FADs as part of the assessment of risks from ALDFG for these gear types as it is unclear what proportion of global effort by these gears occurs on FADs.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to bycatch impacts, there are some important considerations. First, fleets that employ selective gears (e.g., troll and surface methods) often lack observer coverage, and thus, bycatch impacts are relatively unknown compared to longline and purse seine fleets (Miller et al, 2017). Second, some highly selective fishing methods require a substantial quantity of baitfish whose sustainability and capture emissions were not assessed here (Gillett, 2011).…”
Section: Study Limitationsmentioning
confidence: 99%
“…The trade-offs inherent in these catches are illustrated across different gear types. More selective fishing gears such as pole-and-line and trolling gears typically have limited bycatch but lower catch rates (Miller et al, 2017). Meanwhile, less selective gears such as longlines and purse seines are capable of catching more fish at a time, which is often also associated with a greater bycatch risk (Watson et al, 2009;Gilman, 2011;Watson and Bigelow, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the Maldives skipjack and small yellowfin tuna are caught by targeting (i) free swimming schools (45.4%), (ii) logs or other drifting objects (11.3%), (which includes drifting fish aggregating devices (DFADs) deployed by purse seiners that pass through the Maldives EEZ), (iii) seamount associated schools (10.4%), and (iv) anchored fish aggregating devices (AFADs) (32.8%) [33]. Studies showed that AFADs related catches contribute to nearly one third of all the tuna caught by pole-and-line in the Maldives [33]. Traditionally, Maldivian tuna fishers have fished at logs or drifting objects associated schools for centuries and they refer to these objects that attract tuna as 'oivaali' (a local name given to drifting objects).…”
Section: Plos Onementioning
confidence: 99%